2017
DOI: 10.1088/1741-2552/aa7e82
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent adaptation improves robustness of myoelectric control for upper-limb prostheses

Abstract: This is the first online evaluation of a method integrating information from multiple on-board prosthesis sensors to modulate the output of a machine-learning-based myoelectric controller. The proposed scheme is general and presents a simple, non-invasive and cost-effective approach for improving the robustness of myoelectric control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Semi-autonomous control using computer vision can allow simple control of advanced bionic limbs, thereby improving user experience and potentially decreasing rejection rates. In addition, recent studies in conventional human-machine interfacing also propose to equip a prosthesis with advanced sensors that might require complex data processing; e.g., inertial measurement units [50], electronic skins [51], musculoskeletal modeling [52], high-density EMG [53]. To support these developments as well as general user demands for better control and functionality [54], modern prostheses will need to integrate improved processing capabilities (see [5]).…”
Section: Discussionmentioning
confidence: 99%
“…Semi-autonomous control using computer vision can allow simple control of advanced bionic limbs, thereby improving user experience and potentially decreasing rejection rates. In addition, recent studies in conventional human-machine interfacing also propose to equip a prosthesis with advanced sensors that might require complex data processing; e.g., inertial measurement units [50], electronic skins [51], musculoskeletal modeling [52], high-density EMG [53]. To support these developments as well as general user demands for better control and functionality [54], modern prostheses will need to integrate improved processing capabilities (see [5]).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a trade-off has to be made when deciding the level of sharing of control between the user and the hardware, and an intermediate level of interaction between the two was favored (Cipriani et al, 2008 ). Following this idea, context-dependent switching scheme can be found in several recent studies to control kinematics of the prosthetic hands based on sEMG pattern (Amsuess et al, 2016 ), limb kinematics and/or grasp force (Jiang et al, 2013 ; Patel et al, 2017 ), or vision (Markovic et al, 2014 , 2015 ; Ghazaei et al, 2017 ). It has been argued that such semi-autonomous shared control can help to shield some low level execution details and decreases cognitive burden while maintaining high level function (Castellini et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is because their reliance on a potentially incorrect underlying model may result in a context that is isolated from, and possibly in disagreement with, the real-world environment. Others have sought to improve situational context by including additional sensors, such as cameras embedded within the prosthesis [37][38][39]. These are examples of contextaware myoelectric control systems that incorporate environmental information into their classifier inputs (see Fig.…”
Section: Contextmentioning
confidence: 99%